Rosuvastatin induced pruritus and dizziness: a case report - Rohra, Divya J.; Lazarevic , Milenko (International Journal of Research in Medical Sciences, 2024)
Drug-associated adverse reactions can manifest with a wide range of symptoms. Some are widely reported, while others are less commonly observed. This case report describes a 36-year-old woman who was prescribed rosuvastatin to manage her elevated triglyceride levels and experienced adverse effects like pruritus and dizziness within ten days of starting the medication. After discontinuing rosuvastatin, her dizziness resolved immediately, and the pruritus diminished over the following two weeks, eventually subsiding completely. This case underscores the importance of considering Rosuvastatin-related adverse effects when evaluating patients with similar complaints.